The impact of noise exposure and work posture on job stress in a food company. - Chaharaghran, Fatemeh; Tabatabaei, Shahnaz; Rostamzadeh, Sajjad (Work, 2022)
BACKGROUND: In most food companies, workers are constantly exposed to non-standard levels of noise. Also, food production processes require intense manual labor and repetitive movements, which may result in musculoskeletal disorders (MSDs). Noise and awkward posture are considered as two important physical factors in the industrialized world, which can related to perceived stress. OBJECTIVE: This study was conducted among food factory workers to investigate the impact of noise exposure and work posture on occupational stress. METHODS: A total of 200 workers were examined in this cross-sectional study. Individual noise exposure was measured by TES-1354 dosimeter (TES, TW) according to ISO 9612. Postural risk and job stress levels were assessed using Quick Exposure Check (QEC), and the Osipow occupational stress questionnaire, respectively. RESULTS: The level of noise exposure and awkward posture were significantly associated with work-related stress.The relationship of gender with occupational stress was also statistically significant. CONCLUSIONS: Considering that the noise exposure and work posture factors are important determinants of work-related stress, a combined approach to eliminate the levels of non-standard noise and inappropriate posture is essential for promoting psychological health in food companies.